Juniper Blue : (A Novel) - Lang, Susan, 1941- (Book collections on Project MUSE., 2006)
Ruth Farley is still on her homestead at the end of a rugged canyon in California's Mojave Desert, still struggling to survive on her own but now also facing the ever-growing responsibilities of motherhood. Her expanding world encompasses the vast panorama of Depression-era Southern California - isolated miners and ranchers striving to hang on until times are better; small-town gossips; Indians trying to preserve their ancient culture and identity; vagrants and breadlines; and the wealth and glitter of the movie industry.